AUTOMATIC CLASSIFICATION AND DETECTION OF COUNTERFEIT BANKNOTES BASED AI (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
On the basis of the look, people can easilydifferentiate banknotes and coin denominations. The coincurrencies can be identified visually impaired people basedon touch, but the note currencies cannot be identified easilyas it has similar texture and appearance, it can be challengingfor visually challenged people to distinguish the currencies. Demonetization has boosted the availability of fake cash inrecent years. People face difficulty in distinguishing betweenreal and fake banknotes because they are unaware of thesecurity elements utilized in modern currencies. Additionally, these fake cash mislead persons who don’t haveproper vision. So, it becomes important to identify thedenominations and detect fake and real banknotes in-orderto avoid the problems caused due to these currencies orbanknotes. This issue highlights the requirement for anaccurate banknote identification model. By spotting thecounterfeit currency, inflation and currency devaluation canbe stopped. The suggested model aims to identify thedenomination and categorize if a money note is real orfraudulent. The banknote denomination is determined using the machine learning algorithms.